Resultados e significados do programa de aquisição de alimentos (PAA) para os agricultores familiares de Pereira Barreto (SP) - Gonzaga, Douglas de Araujo [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The Programa de Aquisição de Alimentos (Food Acquisition Program), usually called PAA, created by the federal government in 2003, aims to ensure quality food and adequate quantity regularly to the people in food insecurity situation. In addition to benefiting the urban population, the PAA strengthens family farming by purchasing their products. The present research had by objective to characterize the producers, the production and analyze the actions taken in terms of benefits generated, found difficulties, evaluation of the results and perspectives of farmers and entities recipients of food, facing the Program. The methods and research techniques applied were based on the use of questionnaires to farmers located in four (re)settlements surrounding Pereira Barreto (SP), and semi-structured interviews directed to presidents of associations and representatives of benefited entities. Among the effects of the program in the rural (re)settlements surveyed, could be inferred that there was an increase of the area and the number of crops; and generation of an extra income on certain regular basis, which led to investments in the allotment and household goods, resulting in greater motivation of farmers to work in the field. It was found that the greatest obstacles faced by producers are the delay of payment for delivered food and difficulties related to the transport of production. Another important fact pointed out by this research is that participation in the PAA didn't result yet, for the vast majority of producers, on expansion of their marketing channels. Regarding the role of associations in the implementation of the PAA, it was found that the president exerts a crucial role for the formation and performance of itself. In a self- evaluation on the quality of food, farmers mostly classified it as high or good quality products, but some philanthropic entities made restrictions on the food's quality and, as a general rule, critical ...

O Programa de Aquisição de Alimentos, conhecido pela sigla do nome do programa PAA, criado pelo governo federal em 2003, tem como meta assegurar alimentos com qualidade e quantidade adequada regularmente às populações em situação de insegurança alimentar. Além de beneficiar a população urbana, o PAA fortalece a agricultura familiar ao adquirir seus produtos. A presente pesquisa objetivou caracterizar os produtores, a produção e analisar as ações desenvolvidas em termos de benefícios gerados, dificuldades encontradas, avaliação dos resultados e perspectivas dos agricultores e das entidades recebedoras dos alimentos, frente ao Programa. Os métodos e as técnicas de pesquisa adotadas basearam-se no uso de questionários aplicados aos agricultores residentes em quatro (re)assentamentos do entorno de Pereira Barreto (SP), e em entrevistas semiestruturadas dirigidas aos presidentes das Associações e aos representantes das entidades beneficiadas. Dentre os efeitos do Programa nos (re)assentamentos rurais pesquisados, pôde-se inferir que houve a ampliação da área e do número de cultivos; e geração de uma renda extra com certa regularidade, o que propiciou a realização de investimentos no lote e em bens para a casa, resultando em maior motivação dos agricultores para o trabalho no campo. Constatou-se que os maiores entraves enfrentados pelos produtores são o atraso do pagamento pelos alimentos entregues e dificuldades em relação ao transporte da produção. Outro fato relevante apontado por esta pesquisa é o que a participação no PAA não resultou ainda, para a grande maioria dos produtores, na expansão de seus canais de comercialização. Sobre o papel das associações na execução do PAA, verificou-se que o presidente exerce função crucial para a formação e o desempenho das mesmas. Em uma autoavaliação acerca da qualidade dos alimentos, os agricultores em sua maioria os classificaram como produto de...
Keywords: Politicas publicas; Assentamentos rurais; Produtos agricolas - Mercado; Public policy